Situational analysis of health surveillance at the human-wildlife interface for preventing zoonoses in Côte d’Ivoire - Dinde, A.O.; Cook, Elizabeth A.J.; Soro, D.; Hung Nguyen-Viet; Bett, Bernard K.; Bonfoh, B. (International Livestock Research Institute, 2024)
Key messages Health monitoring programs exist for human, animal, and environment but are discipline specific. Lack of integrated surveillance systems and scarce wildlife monitoring. National One Health Platform and increasing research on wildlife are creating opportunities for better integration of the wildlife sector into the surveillance systems. Policies are necessary to address surveillance at the human-wildlife interfaces including the wild meat value chain.